A multiscale integrated analysis of six developing countries with established tourism economies: the case of Cuba, Dominican Republic, Jamaica, Malaysia, Jordan, and Tunisia - Valeria Andreoni; Julia Jeyacheya (World Development Sustainability)
This paper investigates the socio-economic and the energy changes that have taken place in six developing countries characterized by established tourism economies. By considering the years 2000 and 2021, the MuSIASEM approach is used to analyse the energy allocation and use that have taken place in Cuba, Dominic Republic, Jamaica, Jordan, Malaysia, and Tunisia. Results show that for all the countries the percentage variation of GDP has been higher than the energy consumption increase, denoting efficiency improvements across all the sectors, with exception of the service compartment of Tunisia and Jamaica. Tunisia has also been the only country to increase the exosomatic metabolic rate of the household and the paid sectors, denoting an energy consumption rise per unit of human time. All the areas have increased the percentage contribution of the service sector to employment and GDP generation. Given the extensive role that tourism activities are playing in these countries, further analysis should be devoted to investigating alterative development approaches and the related sustainability goals.